2002
DOI: 10.1007/s00125-002-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NO-dependent vasodilation in patients with Type II (non-insulin-dependent) diabetes mellitus is restored by acute administration of folate

Abstract: Aims/hypothesis. Patients with diabetes are characterised by endothelial dysfunction and cardiovascular mortality. In particular endothelium-derived nitric oxide has emerged as a first line mechanism against atherosclerosis. Hyperglycaemia causes oxygen radical stress but has also been associated with endothelial nitric oxide synthase uncoupling, both lead to decreased nitric oxide-availability. We recently showed that folate reverses eNOS uncoupling in vitro. Therefore we hypothesise that folate improves endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 47 publications
(64 reference statements)
6
78
0
1
Order By: Relevance
“…In our study, endothelial function in obese children did not improve despite a significant decrease in tHcy. However, direct benefits of folate within 2-4 h on endothelial function, independent of homocysteine lowering, are reported in vitro (13)(14)(15)(16) and in type 1 and type 2 diabetes in our studies and others' (10, 17,18,24,25). Consistent with these findings is the evidence that low RCF independent of homocysteine in adults is associated with increased intima-media thickness (26).…”
Section: Statisticssupporting
confidence: 90%
“…In our study, endothelial function in obese children did not improve despite a significant decrease in tHcy. However, direct benefits of folate within 2-4 h on endothelial function, independent of homocysteine lowering, are reported in vitro (13)(14)(15)(16) and in type 1 and type 2 diabetes in our studies and others' (10, 17,18,24,25). Consistent with these findings is the evidence that low RCF independent of homocysteine in adults is associated with increased intima-media thickness (26).…”
Section: Statisticssupporting
confidence: 90%
“…[7][8][9][10] However, when we started our study, there was limited information in subjects with diabetes mellitus. Using forearm plethysmography, van Etten et al 17 demonstrated that subjects with type 2 diabetes have impaired endothelium-dependent, serotonin-induced vasodilation and mildly reduced endotheliumindependent vasodilation in response to sodium nitroprusside. Acute intra-arterial administration of 5-methyltetrahydrofolate, the active metabolite of folic acid, restored the endothelium-dependent vasodilation, but had no effect on endothelium-independent vasodilation in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that both endothelium-dependent and -independent vasodilation are impaired in this disease (1)(2)(3)(4)(5)(6). This reduction in vascular reactivity has been attributed to decreased endothelial nitric oxide (NO) synthesis (3,4), increased NO degradation (2,6), and/or abnormalities in vascular smooth muscle (3).…”
mentioning
confidence: 99%